Time Delay and Cost Overrun of Road over Bridge (ROB) Construction Projects in India - Venkateswaran, Chandrasekaran Balaji; Murugasan, Rajiah (Penerbit Universiti Sains Malaysia, 2017)
This paper aims at studying the factors that contribute to time delay and cost overrun of Road over Bridge (ROB) projects in India. Data for the research study were collected from 62 respondents, including owners, contractors, and consultants of ROB projects. The literature survey and the questionnaire survey helped in identifying 29 factors. The topmost factors were ranked based on the frequency of occurrences. The correlation among owners, contractors, and consultants on ranking of factors was derived by Spearman rank correlation. Factor analysis was used to classify the factors into groups and identify the key groups responsible for time delay and cost overrun of projects. This study will help all stakeholders of ROB projects in India to understand the factors and thereby reduce time delay and cost overrun as well as expedite their completion.